A Longitudinal Assessment of the Quality of Insulin Prescribing with Different Prescribing Systems - Amandeep Setra; Yogini Jani (MDPI AG, 2021)
Accurate and complete prescriptions of insulin are crucial to prevent medication errors from occurring. Two core components for safe insulin prescriptions are the word 'units' being written in full for the dose, and clear documentation of the insulin device alongside the name. A retrospective review of annual audit data was conducted for insulin prescriptions to assess the impact of changes to the prescribing system within a secondary care setting, at five time points over a period of 7 years (2014 to 2020). The review points were based on when changes were made, from standardized paper charts with a dedicated section for insulin prescribing, to a standalone hospital wide electronic prescribing and medicines administration (ePMA) system, and finally an integrated electronic health record system (EHRS). The measured outcomes were compliance with recommended standards for documentation of 'units' in full, and inclusion of the insulin device as part of the prescription. Overall, an improvement was seen in both outcomes of interest. Device documentation improved incrementally with each system change-34% for paper charts, 23%-56% for standalone ePMA, and 100% for ePMA integrated within EHRS. Findings highlight that differences in ePMA systems may have varying impact on safe prescribing practices.